New navigation competencies required for an updated STCW convention - Barsan, Eugen; Hanzu-Pazara, Radu; Arsenie, Paulica (2007)
IMO started to request uniform international standards for the seafarers in the early 80ties. After fifteen years a revision of the STCW78 Convention was already needed, and an improved STCW 95 Convention was adopted. In the last ten years, the ship bridge change rapidly, a lot of new technologies have been implemented with a declared objective to increase safety of navigation. We think that it is time to update some of the STCW95 requirements regarding competencies regarding navigation at operational and management level and also some of the provisions related to the implementation of the Convention at national level. Our paper intends to underline some of these aspects that in our opinion must be revised and/or supplemented, including enforcement for theoretical training in maritime education institution and extended use of simulators in the training process. We will also state our opinion related to the necessity of cancelling some IMO courses from the compulsory list and make proposals for another IMO courses that had to became essential
Bibliografija: 7 jed
Sažetak
Keywords: Pomorsko obrazovanje